2016 IEEE Intl Conference on Computational Science and Engineering (CSE) and IEEE Intl Conference on Embedded and Ubiquitous Co 2016
DOI: 10.1109/cse-euc-dcabes.2016.155
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Channel Model for Emerging Wireless Networks-on-Chip

Abstract: Abstract-Recently wireless Networks-on-Chip (WiNoCs) have been proposed to overcome the scalability and performance limitations of traditional multi-hop wired NoC architectures. However, the adaptation of wireless technology for on-chip communication is still in its infancy. Consequently, several challenges such as simulation and design tools that consider the technological constraints imposed by the wireless channel are yet to be addressed. To this end, in this paper, we propose and efficient channel model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In [17], authors have proposed a multi-channel WiNoC platform and in [18], a communication channel in the Ka band is proposed to improve the on-chip communication of many-core chips. A parameterizable wireless channel model is proposed in [19] to evaluate the losses in WiNoC and to simulate the platform better. In [20], authors have shown the impact of a semi-realistic multipath wireless channel over conventional WiNoC modulation scheme and have proposed a digital transceiver architecture.…”
Section: Winoc Without Securitymentioning
confidence: 99%
“…In [17], authors have proposed a multi-channel WiNoC platform and in [18], a communication channel in the Ka band is proposed to improve the on-chip communication of many-core chips. A parameterizable wireless channel model is proposed in [19] to evaluate the losses in WiNoC and to simulate the platform better. In [20], authors have shown the impact of a semi-realistic multipath wireless channel over conventional WiNoC modulation scheme and have proposed a digital transceiver architecture.…”
Section: Winoc Without Securitymentioning
confidence: 99%
“…Few prior works have introduced some interesting channel features that could have been considered for WiNoC simulations. For instance, a two-ray signal propagation and molecular absorption attenuation (MAA) were introduced in [13] and [14], respectively. Further, a proof-of-concept study was performed in [15] using isotropic integrated dipole antennas in ka band (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Related Workmentioning
confidence: 99%
“…The WiNoC channel must be modeled considering the parasitic phenomena introduced by the physical structure and electrical properties of all the components inside the chip and by the chip package [14]. Therefore, the design of an accurate channel model for WiNoC applications is important but it is also a complex task.…”
Section: Channel Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conventional metal based interconnections are insufficient to satisfy the needs of both low latency and high performance as the number of cores increases. Alternative fabrics and architectures, such as photonic NoC [12], nanophotonic NoC [13], three-dimensional (3D) NoC [14], Wireless NoC (WiNoC) [15][16][17][18][19], and hybrid WiNoC [20][21][22][23], have been then investigated.…”
Section: Introductionmentioning
confidence: 99%